CONSTRAINTS IN LEARNING SPANISH AS A FOREIGN LANGUAGE: A MIXED-METHOD STUDY - B. Beralde, Ma. Kristine; De Castillo, Shirly O.; M. Obrero, Ma. Seris (SIGEH ELT : Journal of Literature and Linguistics, 2023)
This study aimed to explore the constraints faced by students in learning a foreign language at Camarines Sur Polytechnic Colleges. The researchers formulated two main questions in this study: (1) What are the constraints in learning Spanish as a Foreign language learning in terms of (a) learning differences, (b) learning language material resources, and (c) classroom activities?; (2) What are the factors that affect the constraints in learning Spanish along with (a) learning differences, (b) learning language material resources, and (c) classroom activities? To answer the research questions, the researchers utilized a mixed-method research design. The researchers used a survey questionnaire for the data gathering. The researchers tabulated and calculated the weighted mean of each student‟s perception based on the questionnaire result given to them. Moreover, the researchers interviewed students chosen based on the criterion to triangulate the study results. In addition, thematic analysis was used to analyze the collected data from the transcribed interviews. Research ethics was properly observed during data collection. Furthermore, the findings showed that the constraints faced by the students in Spanish language learning are negative attitude, low motivation, usage of the different learning styles of students, ineffective language material resources, and classroom activities giving less opportunity for students to practice or perform their Spanish speaking skills. The results also revealed the factorsthat cause these constraints.